School feeding and family farming in coast municipalities of Rio Grande do Sul: an analysis from nutritionists' perception - Machado Germano, Arlan; Cassel Bueno, Marilene; Ramos Kirsten, Vanessa (Universidade Federal Rural do Rio de Janeiro, 2020)
This study aimed to analyze the perception and dialogue among nutritionists in relation to the purchase of products from family farmers for school meals in municipalities on the coast of the state of Rio Grande do Sul. This is a qualitative study carried out in six municipalities that included participation of nutritionists in charge of school meals. All nutritionists reported a positive perception regarding the Brazilian National School Feeding Program (PNAE - Programa Nacional de Alimentação Escolar) for both farmers and the municipality. Articulation often takes place through the Technical Assistance and Rural Extension Company, Education Office and Agriculture Office. Cited as a source of food of social origin and inclusion, PNAE also develops the local economy. The main difficulties faced were short workload to work in the municipality; agriculture not being characteristic on the coast; and lack of dialogue between all parties involved. Therefore, for PNAE to be effective, it is necessary collaboration of all actors involved, incentives and local support with active and permanent action.